2018
DOI: 10.1097/md.0000000000013292
|View full text |Cite
|
Sign up to set email alerts
|

Telerehabilitation in individuals with severe acquired brain injury

Abstract: Background:Severe acquired brain injury (SABI) rehabilitation should be as intensive and long as to allow the patients get the best independence and quality of life (QoL), but facing with the rehabilitation socioeconomic burden. Telerehabilitation (TR) could supply frail subjects requiring long-term rehabilitation.Methods:A multicenter, prospective, parallel design, single-blind trial will be conducted at the IRCCS Neurolesi Bonino Pulejo (Messina, Italy) and IRCCS Hospital San Camillo (Venice, Italy) involvin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
3

Relationship

4
6

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 36 publications
1
14
0
Order By: Relevance
“…The potential of telerehabilitation could be confirmed by Calabrò et al (95), who are conducting a multicenter study on the role of cognitive telerehabilitation in individuals with ABI, evaluating the functional recovery of patients, psychological well-being, the burden of caregivers with a cost-effectiveness analysis.…”
Section: Neurological Diseases In Adulthoodmentioning
confidence: 93%
“…The potential of telerehabilitation could be confirmed by Calabrò et al (95), who are conducting a multicenter study on the role of cognitive telerehabilitation in individuals with ABI, evaluating the functional recovery of patients, psychological well-being, the burden of caregivers with a cost-effectiveness analysis.…”
Section: Neurological Diseases In Adulthoodmentioning
confidence: 93%
“…Professionals reported a high level of agreement with the statement regarding the potential effect of telerehabilitation in enhancing the sense of competence of patients and caregivers in relation to the disability. This perception, based on a screen-mediated observation during remote treatment, has been assessed in previous studies in which professionals' feedback during sessions has shown to make patients and caregivers proactive, thus empowering their ability to care for their loved ones (23,(49)(50)(51)(52)(53)(54)(55)(56)(57)(58)(59). Based on the logit regression, remote media skilled professionals and those below the age of 40 have a higher probability to report that telerehabilitation could favor the patient's/family's sense of competence.…”
Section: Perception Of Rehabilitation Professionalsmentioning
confidence: 99%
“…The Hub Center, in turn, sends those patients with less severe pathologies to the peripheral spoke center closest to their home. Moreover, telerehabilitation can be provided directly by the Hub Center using the Virtual Reality Rehabilitation System, so that spoke center inpatients may benefit from skilled therapists and clinicians (Calabrò et al , 2018).…”
Section: Toward a New Hsmmentioning
confidence: 99%